Unraveling the Interdependence of Inputs and Outputs in the Business Sector: A Case Study - Sahani, S.K.; Sah, R.; Kumari, S.; Sahani, K.; Prasad, K.S. (Darul Yasin Al Sys, 2023)
This research project explores the application and utility of input-output analysis as a pivotal decision-making tool in the business sector. Input-output analysis (I-O) is a quantitative economic modeling technique that assesses the interdependencies among various sectors of an economy. Understanding the concept, application, strategic planning, and resource allocation within the input-output model facilitates effective decision-making in business operations. This project offers guidance for determining, analyzing, evaluating, and selecting across different business levels and sectors. The primary tool employed in the I-O process is the input-output analysis table. In this project, we utilize Leontief's model, specifically the open model, to determine the required resources to meet an increase in demand. Data collection methods for this research encompass data analysis, sample surveys, content analysis, business analysis, data preprocessing, and historical observations. It is important to note that this research project focuses exclusively on the business sector and its operational facets. Various businesses and their operations are examined to provide examples and insights into the implementation of I-O in the production sector. The chosen I-O model for this report is Leontief's model. Through the findings of this research report, it is evident that I-O can be effectively employed in the business sector to inform decisions related to inputs and outputs, promoting smooth economic progress. Ultimately, this project sheds light on the intricate interdependencies of inputs and outputs within the business sector.